Good science depends on good peer review - Michael E. Hochberg (Ideas in Ecology and Evolution, 2015)
I argue that the quality of both scientific research and how it is communicated is maintained and improved through a process analogous to Darwinian evolution. Maintaining status quo or achieving scientific advances are potentially threatened by ‘costs’, including costs in the effort required to maintain current or attain higher scientific quality, and financial costs of conducting high-level research. I describe through analogy with Darwinian evolution how, without peer-review and editorial oversight, scientific quality is expected to decrease on average in the long run. Several mechanisms are presented which, taken together, can contribute to limiting or counteracting this effect—some of the most promising being reviewer rewards, journal peerage, and education. I conclude that the scientific community needs to be proactive in promoting peer review and the reviewer commons, and ultimately scientific quality, because the erosion effect may be gradual and barely noticeable in the short-term, but have substantial effects over the long-term.